An assessment of innovative practices/technologies in managing large and extra-large classes for effective teaching and learning of science - De Asis, Rodelio G. (Quezon City University of the Philippines Diliman, 2012)
This study assessed and compared the innovative practices/technologies in managing large (L) and extra-large (XL) classes of two (2) of the five (5) schools that qualified to the DOST-SEI project entitled "Search for Innovative Practices in Managing Large and Extra-Large Class Sizes for the Effective Teaching and Learning of Science and Mathematics". These schools are the Navotas National High School (NNHS), Navotas City and San Isidro National High School (SINHS), Makati City. It also determined if such innovative practices/technologies have relationships with how the students perform in the class. The NNHS has an XL class in third year and Chemistry is the subject that was assessed while SINHS has a L class in fourth year high school and Physics is the subject that was studied. The Pre and Post Test instruments were developed and administered by the University of the Philippines-National Institute for Science and Mathematics Education (UP-NISMED) to the participating schools while the Student Engagement Instrument was adopted to the foreign source and administered by the author to the said two respondent schools. Descriptive statistics such as frequency, percentage, mean and standard deviations were used to assess the innovative practices/technologies of the said schools. The analysis applied to the data gave the following findings : Pre and Post Tests NNHS - The paired samples statistics for Science 4 (Physics) indicates that the post-test percent mean score (50.1905 percent) is higher than the pre-test (28.3810 precent). The paired samples correlations for Science 4 (Physics) shows that there is a positive correlation of 0.194 between the two variables, which implies that the students who did well on the pre-test also did well on the post test. The paired samples t test shows that the significance is 0.000, which means that there is a significant difference between the pre and post test scores. The result implies that the implementation of the innovative practice/technology like the M-CART improved the performance of the Science 4 (Physics) students of NNHS. SINHS - The paired sample statistics for Science 3 (Chemistry) indicates that the post-test percent mean score (42.7489 percent) is higher than the pre-test (33.9827 percent). The paired samples correlation for Science 3 (Chemistry) shows that there is a positive correlation of 0.194 between the two variables, which means that the students who did well on the pre-test also did well on the post test. The paired samples t test shows that the significance is 0.000, which means that there is a significant difference between the pre and post test scores. The result implies that the implementation of the innovative practice/technology like i-motion improved the performance of the Science 3 (Chemistry) students of SINHS. Student Engagement - The implementation of the M-CART in NNHS slightly increases the average of students that "always" engage in class (from 35 percent before to 49.25 percent). There is a slight decrease (from 57 percent to 46.27 percent), however, on the average of students that "very often" engages in class. Hence, the M-CART has an effect on engaging the students in their class. The implementation of i-motion in SINHS resulted in a slight decrease (about 19 percent difference) in the number of students that responded "very often" before and after the implementation of the innovation. On the other hand, there is a huge increase (from 20 percent to 43 percent) on the response of students on the "always" scale, which implies that the i-motion helped the students in engaging in the class activities.
With the above findings, the following are the conclusions and recommendations : Conclusions : The following conclusions were made based on the findings of the study : The performance of students in both schools (NNHS and SINHS) in Science 4 (Physics) and Science 3 (Chemistry) improved as a result of the implementation of innovative teaching practices/technologies like M-CART and i-motion. This can be shown by the increase in mean scores of the students who took the pre-and post tests. Moreover, the statistical analysis conducted showed that there is a significant difference in mean scores of the students in the pre and post tests. Moreover, the implementation of M-CART and i-motion improved the student engagement in the class. This can be shown by the increase in the average of students that indicate that they "always" engage in the class activities and a slight decrease on the average of students that indicate that they "very often" engage in the class activities. The findings support the earlier studies that learning is higher when information was presented via computer-based systems than traditional classroom lectures. Students have better attitudes towards learning when using innovative teaching strategies/technologies because it presents true-to-life situations that students may face every day and confronted with real problems that have real consequences. Recommendations : With the earlier findings and conclusions, the following recommendations are offered: Considering the positive student engagement and general performance of the sample schools in the pre and post tests, science teachers and educators are encouraged to explore more innovative teaching methods, strategies and technologies that will help learners to improve their performance in class. The interactive courseware on science and mathematics for the first and second year high schools, developed by the Science Education Institute (SEI) and the Advanced Science and Technology Institute (ASTI) of the Department of Science and Technology (DOST) would help the educators in teaching science and mathematics classes. The use of the interactive modules gives the students not only the opportunity to experience something closely related to real life with the introduction of simulations, animated graphics and images with synchronized voice-overs, but also involves the learner in a vicarious experience of events or process thus, engaging the students to a different, fascinating and virtually realistic opportunity to learn about scientific phenomena. Because of this, students will enjoy the lessons more, increase their learning and keep their interest and reinforces their skills. The modules also empower teachers to more effectively and efficiently meet the challenges of education in today's increasingly technology-infused schools, recognizing and pursuing opportunities to integrate computer-based technologies into the teaching-learning process. It will serve as an effective tool for secondary level teachers in motivating their students to learn and participate in class discussions. Aside from the science classes, similar studies should be conducted to other subjects not examined in this study. It is evident in this study that students can only learn what their teachers are able to demonstrate. The teachers must be competent in the subjects that they are teaching to be able to produce competent students. Therefore, it is recommended that science teachers must be trained not only in instructional methods but also in communication skills to be able to communicate well what they are teaching to students. Based on the class observation, it is evident that due to the overcrowded classroom, the voice of the teachers cannot be heard at the back portion of the room. Hence, it is recommended that the schools or the teachers themselves must provide a public address system so that their lectures must be clearly delivered to the students.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Educational innovations; Teaching -- Aids and devices; Educational technology; Effective teaching; Science, Learning; Innovative practices